High‐resolution imaging of defects in CdTe solar cells using thermoreflectance. Issue 24 (1st November 2013) - Katz, N.; Patterson, M.; Zaunbrecher, K.; Johnston, S.; Hudgings, J.
Abstract : Thermal imaging of solar cells is important for diagnosing non‐uniform operation or point defects, which can reduce cell efficiency. However, imaging with infrared light is impractical for superstrate CdTe cells because the glass substrate blocks transmission of light. It is shown that thermoreflectance – a lock‐in technique that detects changes in the reflectivity of visible light – can circumvent this problem and achieve thermal images with spatial resolution limited only by the imaging wavelength. The diagnostic is used to show that a particular defect is a resistive shunt.